Las competencias de educación física y el fortalecimiento de la convivencia escolar en estudiantes de vi ciclo de la institución educativa N° 601014 República del Perú, Yavarí 2024 - Acosta Holanda, Damaris (2025)
This research aimed to analyze the relationship between physical education competencies and the strengthening of school coexistence in students of the VI Cycle of the educational institution No. 601014 República del Perú, Yavarí 2024, in response to the question of the problem: Which is the relationship between physical education competencies and the strengthening of school coexistence in students of the VI Cycle of the educational institution Nº 601014 República del Perú, Yavarí 2024? For this, 111 students from the institution were used as the population and sample. The research was non-experimental, and the methodology of the research was a correlational field. To collect the data, the observation approach was used, with two questionnaires, one for each variable, which had been previously validated by experts. The results show that the student's t-test statistic = 5.232, with a bilateral significance of 0.000 and a confidence level of 95%, which confirms that there is a difference between the competency to develop autonomously through their motor skills and the school coexistence in students of the VI Cycle of the educational institution No. 601014 República del Perú, Yavarí, thereby testing the study hypothesis.